Failure to thrive and hypergammaglobulinemia in a 13-year-old girl with Castleman Disease, a case report - Van Parys, Helene; Tuerlinckx, David; Chantrain, Christophe; Somja, Joan; Beckers, Dominique (Belgian Journal of Paediatrics, 2023)
Castleman disease is a rare, lymphoproliferative, non-malignant disorder with two subtypes, unicentric or multicentric, depending on the number of lymph node regions affected. Clinical symptoms may be extremely variable often making the diagnosis difficult or leading to delayed diagnosis. We describe a case of failure to thrive associated with late puberty, and severe hypergammaglobulinemia. Through this case report, we aim to recall the clinical features of this rare disorder and to insist on the importance of a broad differential diagnosis in the presence of failure to thrive especially with abnormal biochemical features.